2007
DOI: 10.1158/0008-5472.can-06-4038
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER-2/neuin Early Breast Cancer Development Using Dendritic Cells with Staged Interleukin-12 Burst Secretion

Abstract: Overexpression of HER-2/neu (c-erbB2) is associated with increased risk of recurrent disease in ductal carcinoma in situ (DCIS) and a poorer prognosis in node-positive breast cancer. We therefore examined the early immunotherapeutic targeting of HER-2/neu in DCIS. Before surgical resection, HER-2/ neu pos DCIS patients (n = 13) received 4 weekly vaccinations of dendritic cells pulsed with HER-2/neu HLA class I and II peptides. The vaccine dendritic cells were activated in vitro with IFN-; and bacterial lipopol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
242
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(258 citation statements)
references
References 43 publications
5
242
1
3
Order By: Relevance
“…Specifically relevant to this study, the higher risk of recurrence associated with Her-2 positivity suggests the possibility of targeted therapy for patients with Her-2-positive tumors. Czerniecki et al 34 found that when patients who had Her-2-positive DCIS tumors were vaccinated with dendritic cells carrying Her-2 peptides, an inflammatory response resulted in tumorlytic antibodies, and a significant number of patients had decreased Her-2 expression within their tumor. The National Surgical Adjuvant Breast and Bowel Project (B-43) is currently comparing trastuzumab (Her-2-targeted therapy) with radiation versus radiation alone for women with Her-2-positive DCIS treated with lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically relevant to this study, the higher risk of recurrence associated with Her-2 positivity suggests the possibility of targeted therapy for patients with Her-2-positive tumors. Czerniecki et al 34 found that when patients who had Her-2-positive DCIS tumors were vaccinated with dendritic cells carrying Her-2 peptides, an inflammatory response resulted in tumorlytic antibodies, and a significant number of patients had decreased Her-2 expression within their tumor. The National Surgical Adjuvant Breast and Bowel Project (B-43) is currently comparing trastuzumab (Her-2-targeted therapy) with radiation versus radiation alone for women with Her-2-positive DCIS treated with lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that DCs with staged IL-12 burst secretion significantly enhanced HER-2/neu-specific CD8 Ăž T-cell responses in clinical trials. 25 Therefore, DCs engineered to express both breast cancer Ag and cytokines may further enhance the antitumor immunity in DC-based vaccines of breast cancer for both prevention of breast cancer development and treatment of early breast cancer. Construction of fiber-modified AdV ( RGD AdVHER-2/TNF) expressing both HER-2/neu and inflammatory cytokine TNF-a and evaluation of the potential therapeutic effect of the AdV-transfected DC vaccine in treatment of early breast cancer in the Tg model are currently underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…24 and stimulate antitumor immunity against challenge of HER-2/neu-positive tumor cells in vivo 22,23 leading to phaseI/II clinical trials. 25,26 However, there are limited studies evaluating the use of HER-2/neutargeted DC-based vaccination in rat HER-2/neu-gene transgenic (Tg) mice with self HER-2/neu tolerance. 27 We have previously demonstrated that vaccination of DCs transfected with AdVHER-2/neu stimulates HER-2/neuspecific CD8 Ăž CTL responses and immunity against challenge of HER-2-expressing colon cancer cells MCA26/HER-2 in wild-type animal model.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, 13 patients with HER2 over-expressing ductal in situ carcinoma were injected with DCs loaded with a mixture containing 6 HLA-I-and HLA-II-restricted peptides (i.e., 3 HER2 ECD-derived peptides and 3 HER2 ICD-derived peptides) once a week for 4 weeks before surgery [45]. Immunized patients developed a specific immune response against the peptides and presented high levels of CD4 ?…”
Section: Clinical Trialsmentioning
confidence: 99%